Human umbilical cord stem cell encapsulation in novel macroporous and injectable fibrin for muscle tissue engineering - Liu, Jun (2012)
There has been little research on the seeding of human umbilical cord mesenchymal stem cells (hUCMSCs) in three-dimensional scaffolds for muscle tissue engineering. The objectives of this study were: (i) to seed hUCMSCs in a fibrin hydrogel containing fast-degradable microbeads (dMBs) to create macropores to enhance cell viability; and (ii) to investigate the encapsulated cell proliferation and myogenic differentiation for muscle tissue engineering. Mass fractions of 0–80% of dMBs were tested, and 35% of dMBs in fibrin was shown to avoid fibrin shrinkage while creating macropores and promoting cell viability. This construct was referred to as “dMB35”. Fibrin without dMBs was termed “dMB0”. Microbead degradation created macropores in fibrin and improved cell viability. The percentage of live cells in dMB35 reached 91% at 16 days, higher than the 81% in dMB0 (p < 0.05). Live cell density in dMB35 was 1.6-fold that of dMB0 (p < 0.05). The encapsulated hUCMSCs proliferated, increasing the cell density by 2.6 times in dMB35 from 1 to 16 days. MTT activity for dMB35 was substantially higher than that for dMB0 at 16 days (p < 0.05). hUCMSCs in dMB35 had high gene expressions of myotube markers of myosin heavy chain 1 (MYH1) and alpha-actinin 3 (ACTN3). Elongated, multinucleated cells were formed with positive staining of myogenic specific proteins including myogenin, MYH, ACTN and actin alpha 1. Moreover, a significant increase in cell fusion was detected with myogenic induction. In conclusion, hUCMSCs were encapsulated in fibrin with degradable microbeads for the first time, achieving greatly enhanced cell viability and successful myogenic differentiation with formation of multinucleated myotubes. The injectable and macroporous fibrin–dMB–hUCMSC construct may be promising for muscle tissue engineering applications.